IDENTITAS VISUAL BUDAYA JEPANG DALAM MANGA DEMON SLAYER: KIMETSU NO YAIBA - Ramdhan, Asep; Prayoga, Candra (INSIDE : Jurnal Desain Interior, 2025)
The manga "Demon Slayer: Kimetsu no Yaiba," which has gained global popularity, not only offers an engaging narrative but also showcases the richness and diversity of Japanese cultural elements. This study aims to identify and analyze cultural symbols, traditional aesthetics, and historical representations integrated into the manga's visualization. The method used is documentation analysis, focusing on visual elements such as Ukiyo-e art, Calligraphy, Yokai, Character Design, and Backgrounds as traditional symbols reflecting Japanese cultural values. The study's results indicate that "Demon Slayer: Kimetsu no Yaiba" successfully combines classic Japanese cultural elements with a modern narrative, creating a work that is not only entertaining but also educational in introducing Japanese culture to the international audience. These findings affirm the importance of manga as an effective medium for disseminating and preserving cultural identity in the era of globalization.